The power - Alderman, Naomi (UK : Viking, 2016)
'She throws her head back and pushes her chest forward and lets go a huge blast right into the centre of his body. The rivulets and streams of red scarring run across his chest and up around his throat. She'd put her hand on his heart and stopped him dead.' Suddenly tomorrow or the day after girls find that with a flick of their fingers, they can inflict agonizing pain and even death. With this single twist, the four lives at the heart of Naomi Alderman's extraordinary, visceral novel are utterly transformed, and we look at the world in an entirely new light. What if the power to hurt were in women's hands?
Keywords: Teenage girls -- Fiction; Dystopias